Typology, topography and tectonics – Categories and models for the urban project - Santiago Gomes (Agathón)
If there is to be a ‘new urbanism’ – Koolhaas wrote in 1995, after declaring its death – it will be the staging of uncertainty. Mutation, unpredictability and indeterminacy characterise the contemporary urban question and are generating, after the initial bewilderment, disciplinary developments that proceed in search of hybrid forms of Planning, less and less conformative and prescriptive. This contribution – placed inside this process, which calls for a redefinition of the tools and categories of reading, design, and management of transformations – proposes the construction of a theoretical-methodological framework based on the actualisation of the concepts of Typology, Topography and Tectonics and advances concrete operational hypotheses for the regulation, prefiguration and activation of transformations from an inclusive transdisciplinary perspective.